Effect of inoculants combining Lactobacillus buchneri strain LN40177 in different strata of the silo - Ribas, Tânia Mara Becher; Neumann, Mikael; Souza, André Martins de; Dochwat, André; Almeida, Eduardo Rodrigues de; Horst, Egon Henrique (Acta Scientiarum. Animal Sciences, 2019)
The objective of this work was to evaluate the chemical composition and rumen disappearance rate of dry matter of corn silages with inoculants combining L. buchneri strain LN40177 in different strata of the silo. The experimental design was a 3x2 randomized complete block design, with three treatments: Control: corn silage without inoculant; 11CFT: corn silage with inoculant which combines L. buchneri strain LN40177 (1.1 x 1011 CFU g-1) with L. casei (1.1 x 1011 CFU g-1); and 11C33: corn silage with inoculant which combines L. buchneri strain LN40177 (1.1 x 1011 CFU g-1) with L. plantarum (1.1 x 1011 CFU g-1) and Enterococcus faecium (1 x 1010 CFU g-1), associated with two strata of the silo (lower and upper). The silage inoculated with 11C33 presented higher contents of crude protein and NDF and lower hemicellulose content in relation to the control treatment and 11CFT. The use of both inoculants resulted in silages with higher concentrations of soluble nutrients. Lower stratum silage had a higher rumen disappearance rate of dry matter compared to the upper stratum. In general, the combinations of L. buchneri promoted nutritional improvements in corn silage, but in presence of L. casei, there were more outstanding improvements.